2016
DOI: 10.1038/srep27585
|View full text |Cite
|
Sign up to set email alerts
|

Information content and acoustic structure of male African elephant social rumbles

Abstract: Until recently, the prevailing theory about male African elephants (Loxodonta africana) was that, once adult and sexually mature, males are solitary and targeted only at finding estrous females. While this is true during the state of ‘musth’ (a condition characterized by aggressive behavior and elevated androgen levels), ‘non-musth’ males exhibit a social system seemingly based on companionship, dominance and established hierarchies. Research on elephant vocal communication has so far focused on females, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 63 publications
(118 reference statements)
4
57
0
Order By: Relevance
“…The formant frequencies and the absolute fundamental frequency were the most informative of the acoustic parameters analysed. Stoeger and Baotic () also found that larger and older males (shoulder height above 3 m and over 25 years old) had an estimated mean vocal tract length of 3.21 m ± 0.51 SD, and that vocal tract length was positively correlated with formant frequency. For younger and smaller males (aged under 25 and less than 3 m tall) the mean vocal tract length estimated from the formants was 2.36 m ± 0.26 SD, similar to that of adult females (Stoeger & Baotic ).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The formant frequencies and the absolute fundamental frequency were the most informative of the acoustic parameters analysed. Stoeger and Baotic () also found that larger and older males (shoulder height above 3 m and over 25 years old) had an estimated mean vocal tract length of 3.21 m ± 0.51 SD, and that vocal tract length was positively correlated with formant frequency. For younger and smaller males (aged under 25 and less than 3 m tall) the mean vocal tract length estimated from the formants was 2.36 m ± 0.26 SD, similar to that of adult females (Stoeger & Baotic ).…”
Section: Resultsmentioning
confidence: 92%
“…, Stoeger et al. , Stoeger & Baotic , Baotic & Stoeger ). Such behavioural contexts included: when individual males were spatially separated from other elephants, when males were approaching another elephant or being approached, during general group locomotion, and physical contact.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations